2007
DOI: 10.1177/0269216307076345
|View full text |Cite
|
Sign up to set email alerts
|

Feeling like a burden to others: a systematic review focusing on the end of life

Abstract: Research into the burden of illness has focused predominantly on family caregivers, with little consideration of the other side of the caregiving relationship-care recipients' perspectives on having become a 'burden to others'. However, there is now a small but growing body of evidence to suggest that worry about creating burden to others is a common and troubling concern for people who are nearing the end of their lives. This concern is referred to as 'self-perceived burden'. The present study provides a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
116
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(137 citation statements)
references
References 105 publications
15
116
0
4
Order By: Relevance
“…For example, in a review of studies on self-perceived burden among patients with advanced illness, McPherson et al noted an influence on such health decisions as foregoing life-sustaining treatment, preparing advance directives, and choosing hospital vs. home care. 10 Interestingly, however, they also noted a strong association between self-perceived burden and requests for physicianassisted suicide among patients who were terminally ill.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in a review of studies on self-perceived burden among patients with advanced illness, McPherson et al noted an influence on such health decisions as foregoing life-sustaining treatment, preparing advance directives, and choosing hospital vs. home care. 10 Interestingly, however, they also noted a strong association between self-perceived burden and requests for physicianassisted suicide among patients who were terminally ill.…”
Section: Discussionmentioning
confidence: 98%
“…In the palliative care setting, it has been associated with expressions of a desire for death and an interest in receiving physician-assisted suicide. 2,10,11 In chronic pain, it has been associated specifically with selfreports of SI. 9,12,13 The second body of research is grounded in the interpersonal theory of suicide, 14,15 which proposes that serious SI depends on the emergence of two psychological precursor conditions, namely, thwarted belongingness and perceived burdensomeness.…”
Section: Introductionmentioning
confidence: 99%
“…16 Ambivalence regarding being a burden to others, yet wanting to be with them, has been described as creating tension for patients, 17,18 and a systematic review regarding burden and end-of-life care identified burden as concerning for patients in Europe (UK) and beyond (Canada, Japan, Kenyan, Korea, and the United States). 19 Continuing to consider sociorelational aspects in future cross-national EoLC research to establish international priority areas for policy and care therefore remains important.…”
Section: Discussionmentioning
confidence: 99%
“…Den autonome veien kan ses som en konsekvens av aktiv dødshjelp, der man stadig ønsker (6,7). I en undersøkelse gjort i Nederland (8) beskrives det at det å vaere trett av livet blir forbundet med tap av autonomi, kontroll, verdighet og uavhengighet -man har mistet lysten på livet.…”
Section: Grenser Flyttesunclassified